1998
DOI: 10.1097/00000478-199807000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Granular Cell Tumor of Soft Tissue

Abstract: Seventy-three cases of malignant, atypical, and multicentric granular cell tumors of soft tissue were studied to clarify criteria for malignancy and prognostic factors. Six histologic criteria were assessed: necrosis, spindling, vesicular nuclei with large nucleoli, increased mitotic activity (> 2 mitoses/10 high-power fields at 200x magnification), high nuclear to cytoplasmic (N:C) ratio, and pleomorphism. Neoplasms that met three or more of these criteria were classified as histologically malignant; those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
326
5
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 685 publications
(341 citation statements)
references
References 27 publications
6
326
5
4
Order By: Relevance
“…GCT that met three or more of these criteria has been classified as histologically malignant, while the presence of one or two criteria defines an atypical GCT. The isolated presence of focal polymorphism can be observed in benign tumors [9]. On the other hand, the benign histopathological picture has been also reported in clinically malignant lesions, which highlights the importance of careful clinical examination.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…GCT that met three or more of these criteria has been classified as histologically malignant, while the presence of one or two criteria defines an atypical GCT. The isolated presence of focal polymorphism can be observed in benign tumors [9]. On the other hand, the benign histopathological picture has been also reported in clinically malignant lesions, which highlights the importance of careful clinical examination.…”
Section: Discussionmentioning
confidence: 95%
“…A classic study reported 39% of survival rate for malignant GCT at a median interval of 3 years and 29% of patients were alive with disease [9]. Six histologic features are used distinguishing benign, atypical, and malignant granular cell tumors: 1) necrosis; 2) spindling; 3) vesicular nuclei with large nucleoli; 4) increased mitotic activity (>2 mitoses/10 high-power fields at 200× magnification); 5) high nuclear to cytoplasmic (N:C) ratio; and 6) nuclearpleomorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse clinical prognostic factors for malignancy are local recurrence, the presence of metastases, old age and size >4 cm [20]. This review highlights that malignant lesions are greater in size (6.34 vs. 2.6 cm), but does not support that patients with malignant lesions are older (45.81 years for benign tumors vs. 40.33 years for the malignant form).…”
Section: Discussionmentioning
confidence: 98%
“…The potentially malignant behavior of these tumors is often ignored, and is discovered only after local recurrence or distant metastases occur, especially when the primary GCT showed no histologic features of malignancy. In an attempt to define clinical features associated with increased malignant potential, Fanburg-Smith et al [20] classified GCTs as malignant if three or more of the following criteria were met: increased mitotic activity, presence of tumor necrosis, large nucleoli, prominent spindling, high nuclear:cytoplasmic ratio and pleomorphism. They also evaluated the immunohistologic criteria and reported that the expression of p53 and Ki-67 was significantly higher in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this lesion is still poorly understood and a matter for discussion; strong evidence of Schwann cell origin has been recently suggested by ultrastructural and immunohistiochemical reports [4^8]. GCT is generally considered a benign tumor, but the malignant counterpart exists, although it is extremely rare [9,10]. This report concerns one case of GCT localized in the intrapancreatic tract of the common bile duct and with a peculiar clinical presentation.…”
mentioning
confidence: 94%